Online Collaborative Learning Platforms in Science: Their Influence on Attitude, Achievement, and Experiences - Gonzales, Glitzy Hart A.; Despe, Kimberly B.; Iway, Larabel J.; Genon, Robie Jane S.; Intano, Jerel O.; Sanchez, Joze Mar P. (Tauladan Fathimah Azzahra, 2023)
This study investigates the influence of online collaborative learning platforms on students’ attitudes, achievements, and experiences. Through a mixed-methods research approach, 100 students from public and private higher education institutes pursuing a Bachelor of Secondary Education major in Science responded to the online survey. At the same time, ten of them participated in the online interviews. Collected data were analyzed using descriptive statistics, t-tests for independent samples, simple linear regression, and thematic analysis. Study findings revealed that the students were generally satisfied (µ=4.08) with the collaborative learning platforms, had positive attitudes toward Science (µ=4.10), and got outstanding Science achievement (µ=1.85). The students from public and private universities were comparable in terms of the use of collaborative learning platforms (p=.302) and students’ satisfaction (p=.868), science attitudes (p=.830), and achievement (p=.158). Moreover, the students were challenged due to unequal participation, different perspectives, and lack of communication and self-confidence. Nevertheless, they also experienced opportunities such as developing social and higher-order thinking skills and values inculcation. In conclusion, collaborative learning platforms have helped and challenged students in learning science.